A Cross-Sectional Study to Evaluate the Relationship of Diabetic Retinopathy with Chronic Kidney Disease in Diabetic Patients in a Tertiary Care Hospital (The Planet, 2024)
Introduction: Diabetes mellitus (DM) and chronic kidney disease (CKD) are common chronic diseases globally and in Bangladesh. Diabetic retinopathy worsens with CKD. This study examines their relationship in diabetic patients at a tertiary hospital. Methods & Materials: This is a cross-sectional observational study conducted at the Department of Ophthalmology, Dhaka Medical College Hospital from Aug 2017 to Oct 2018. A total of 100 diabetic patients were included in the study. Following informed written consent, a physical examination, and relevant investigations were done. In all cases, ethical issues were maintained properly, and collected data were analyzed by SPSS 23. Result: Among 100 participants, the mean±SD age was 57.3±11.1 years (Range 35-85 years) 74% were male and 26% were female. Mean±SD value of HbA1c was (7.4 ±1.8), eGFR was 42.2 ± 32.3mmol/L. Out of 100 patients, 66 had diabetic retinopathy, among them 42 had NPDR and 24 had PDR. Among them 39 CKD patients and 27 0f non CKD patients had DR. CKD patients were found 8 in stage 3B, 10 in stage IV and 32 in stage V. Stage IIIB, stage IV, and stage V had 2, 6, and 31 diabetic retinopathy respectively. Diabetic retinopathy had a positive correlation with low eGFR and CKD stages (p-value
Keywords: Diabetic Retinopathy; Chronic Kidney Disease; Diabetes mellitus; eGFR